Pengaruh Rasio Inlet dan Outlet Bukaan pada Cerobong Surya terhadap Kelajuan Udara Koridor Gedung Jurusan Teknik Arsitektur Politeknik Negeri Pontianak - Dede Irwan; Jockie Zudhy Fibrianto; Dian Perwita Sari (Politeknik Negeri Pontianak, 2020)
Not all humid tropical climate conditions could comfortably support the continuation of tropical human activities. With high humidity, the human who lives in a tropical area tends to need stronger winds so that the water vapor (sweat) that on the skin surface evaporates quickly and provides a cooling effect on the body so that thermal comfort can achieve. Increasing airflow speed can help by the addition of an area both in the inlet area and outlet, as long as the proportion of the area between the area inlet and outlet are appropriate. The quantitative research method used to determine the building condition thermal, such as the condition of the solar funnel with an inlet and outlet ratio of 1: 6 and an inlet and outlet ratio of 1: 1, so that an effective temperature value could be known to determine the thermal comfort level. The analysis result of the air velocity in the solar chimney the Inlet and Outlet ratio of 1: 6 is higher that is equal to 0.32 m / sec than in the Inlet and Outlet ratio solar chimney there is 1: 1 equal to 0.21 m / sec. Air velocity in the solar funnel with a 1: 6 ratio of Inlet and Outlet is 57.6% higher than solar chimney with a 1: 1 ratio of Inlet and Outlet.